Kontrolado ni Girly ang buhay niya (Girly is in control of her life) - Baldoza, Gilbert Mao 1997-; Nicolas A. Deocampo (2018)
"Kontrolado ni Girly Ang Buhay N'ya tells a slice of Girly's life as an unemployed gay teen living below poverty time with his passive mother and an abusive stepfather. He later finds his mother being sexually harassed by her partner. Girly's life changes when the abuses around him repeats to himself and he has nothing left to do but to control his life forward. Kontrolado ni Girly Ang Buhay N'ya is a slice-of-life of a teenage gay oppressed by his environment's economic and sexist factors, in which the characters in the film try to survive and live on to what the realities of their lives give. The framework used in writing the screenplay is Queer Feminism or Patriarchy, Capitalism and Sexual Violence as these reflect on the film's women and queer characters as the primary mobilizers of progression and how both genders share such power to fight against their common oppressors. The film used humanism and its universal language of humanity translated in writing, cinematography, editing, and design in the film's form for its message to transverse divisions of individuality and power and to suture the audience's consciousness in a non-passive familiar transcendence into the film's humanism and reality."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Keywords: Gay teenagers